Agglomerations, tasks and wage growth - Maximilian Perl (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Wage growth is stronger in larger cities, but this relationship holds exclusively for non-manual workers. Using rich German administrative data, I study the heterogeneity in the pecuniary value of big city experience, a measure of dynamic agglomeration economies, and its consequences for the city-size wage gap. After 15 years of work experience in Munich the cumulative earnings premium relative to a median-sized city is 15% for workers in the most manual occupations, 25% for workers in the least manual occupations and 30% for workers in the most analytical occupations. This cumulative wage premium is 3 to 5 times the magnitude of the static city-size wage gap. – – In größeren Städten ist das Gehaltswachstum höher, aber nur für Arbeitnehmer mit nicht-manuellen Tätigkeiten. Diese Studie untersucht die Heterogenität in dem Gehaltszuwachs, der durch Großstadterfahrung entsteht, über unterschiedliche Tätigkeiten hinweg. Die Ergebnisse auf Basis deutscher Sozialversicherungsdaten zeigen, dass die kumulative städtische Lohnprämie für nicht-manuelle Tätigkeiten deutlich ausgeprägter ist. Im Vergleich zu Arbeitnehmern in mittelgroßen Städten verdienten Angestellte nach 15 Jahren Arbeitserfahrung in München in manuellen Tätigkeiten etwa 15%, in nicht-manuellen Tätigkeiten etwa 25% und in analytischen nicht-routine Tätigkeiten etwa 30% mehr. Diese Werte liegen 3- bis 5-mal höher als Schätzungen der statischen (groß-)städtischen Lohnprämie.
Keywords: R10; J31; R23; 330; Cities; agglomeration; tasks; wages; wage growth; Germany